2017
DOI: 10.1186/s40249-017-0301-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of radiotherapy for the treatment of cystic echinococcosis in naturally infected sheep

Abstract: BackgroundRadiotherapy is commonly used to treat cancers. To date, there has been no study focusing on the effects of radiotherapy on hydatid disease in large animals. In this study, we aim to investigate the efficiency and safety of radiotherapy for treating hydatid disease caused by Echinococcus granulosus in naturally infected sheep.MethodsUltrasound was used to screen naturally infected sheep in an echinococcosis endemic area in Xinjiang, China. A computer tomography (CT) scan confirmed the presence of hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…However, in agreement with the hypothesis developed in this review, authors have tested the effect of radiotherapy for the treatment of CE in infected sheep [25]. While the same authors have previously demonstrated that X-ray treatment had a negative impact on the outcome of infected rodents [24], they tested the effect of 30, 45 and 60 Gy, divided into three doses, for 7 days on 20 infected female sheep.…”
Section: Regulated Cell Death Of the Echinococcus Parasitesupporting
confidence: 54%
See 1 more Smart Citation
“…However, in agreement with the hypothesis developed in this review, authors have tested the effect of radiotherapy for the treatment of CE in infected sheep [25]. While the same authors have previously demonstrated that X-ray treatment had a negative impact on the outcome of infected rodents [24], they tested the effect of 30, 45 and 60 Gy, divided into three doses, for 7 days on 20 infected female sheep.…”
Section: Regulated Cell Death Of the Echinococcus Parasitesupporting
confidence: 54%
“…The first approach is to consider the early development of a cyst from approximately 10 stem cells located inside an activated oncosphere in the liver, as a process mimicking cancer [21,42]. Based on that assumption, one could speculate that anti-cancer therapeutic approaches, including radiotherapy, should be tested to induce regulated cell death (RCD) of the parasite [25]. The second option is to address the issue of pro-apoptotic effects of HCF produced during infection of the intermediate host, and to test the hypothesis of potential value of certain specific compounds of this fluid as therapeutic agents for human cancers, including melanoma and breast cancer [11,14,16,39,51].…”
Section: Introductionmentioning
confidence: 99%